Enhanced photoconductive response of ZnO thin films with the impact of annealing temperatures on structural and optical properties - Rajkumar C; Arunachalam Arulraj (Scientific Reports)
Abstract Zinc oxide (ZnO) is a versatile material widely used in optoelectronic devices due to its broad bandgap (3.37 eV), high electron mobility, and significant exciton binding energy (60 meV). In this study, ZnO thin films were fabricated on SiO₂/Si substrates via thermal evaporation, followed by annealing at 400 °C and 600 °C to investigate the effect of thermal treatment on their structural, optical, and photoconductive properties. X-ray diffraction (XRD) analysis confirmed the formation of the hexagonal wurtzite ZnO structure, with improved crystallinity observed at higher annealing temperatures. The photoconductivity of the films demonstrated enhanced response times and self-powered behavior, particularly in the sample annealed at 600 °C. These findings highlight the potential of ZnO thin films for fast-response photodetection applications and show that controlled annealing significantly influences photosensitivity.